The need for multipurpose prevention technologies in sub‐Saharan Africa. (October 2014) - Abdool Karim, S; Baxter, C; Frohlich, J; Abdool Karim, Q
Abstract : Women bear a disproportionate burden of the HIV epidemic in sub‐Saharan Africa and account for about 60% of all adults living with HIV in that region. Young women, including adolescent girls, unable to negotiate mutual faithfulness and/or condom use with their male partners are particularly vulnerable. In addition to the high HIV burden, women in Africa also experience high rates of other sexually transmitted infections and unwanted pregnancies. The development of technologies that can simultaneously meet these multiple sexual reproductive health needs would therefore be extremely beneficial in the African setting.